K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

21 tháng 8 2016

a) (x + 2) . (x + 3) - (x - 2) . (x + 5) = 6                

=> (x . x + 3x + 2x + 2 . 3) - (x . x + 5x - 2x - 2 . 5) = 6

=> (x2 + 5x + 6) - (x2 + 3x - 10) = 6                        

=> x2 + 5x + 6 - x- 3x + 10 = 6

=> 2x +16 = 6       => 2x = -10        => x = -5 

b) (3x + 2) . (2x + 9) - (x + 2) . (6x + 1) = (x + 1) - (x - 6)     

  => (3x . 2x + 3x . 9 + 2 . 2x + 2 . 9) - (x . 6x + 1x + 2 . 6x + 2 .1) = x + 1 - x + 6

=> (6x2 + 31x + 18) - (6x2 + 13x + 2) = 7             

=> 6x2 + 31x + 18 - 6x2 - 13x - 2 = 7

=> 18x + 16 = 7  => 18x = 9  => x = 0,5

c) 3 . (2x - 1) . (3x - 1) - (2x - 3) . (9x - 1) = 0

=> 3(2x . 3x - 2x -3x + 1) - (2x . 9x - 2x -3 . 9x + 3) = 0

=> 3(6x2 - 5x +1) - (18x2 - 29x + 3) = 0

=> (18x2 -15x + 1) -(18x2 - 29x +3) = 0

=> 18x2 - 15x +1 -18x2 + 29x - 3 = 0

=> 14x = 0  => x = 0

21 tháng 8 2016

a)(x+2)(x+3)-(x-2)(x+5)=6

x(x+3)+2(x+3)-x(x+5)+2(x+5)=6

x2+3x+2x+6-x2-5x+2x+10=6

(x2-x2)+(3x+2x-5x+2x)+(10+6)=6

2x+16=6

2x=6-16

2x=-10

x=-10/2

x=-5. Vậy x=-5

b)3x(2x+9)+2(2x+9)-x(6x+1)-2(6x+1)=x+1-x+6

6x2+27x+4x+18-6x2-x-12x-2=7

(6x2-6x2)+(27x+4x-x-12x)+(18-2)=7

18x+16=7

18x=7-16

x=-9/18=-1/2. Vậy x=-1/2

c)[3(3x-1)](2x-1)-(2x-3)(9x-1)=0

(9x-3)(2x-1)-(2x-3)(9x-1)=0

9x(2x-1)-3(2x-1)-2x(9x-1)+3(9x-1)=0

18x2-9x-6x+3-18x2+2x+27x-3=0

(18x2-18x2)+(27x+2x-6x-9x)+(3-3)=0

14x=0

x=0/14

x=0. Vậy x=0

21 tháng 8 2016

a) (x + 2) . (x + 3) - (x - 2) . (x + 5) = 6                    => (x . x + 3x + 2x + 2 . 3) - (x . x + 5x - 2x - 2 . 5) = 6

=> (x2 + 5x + 6) - (x2 + 3x - 10) = 6                          

=> x2 + 5x + 6 - x- 3x + 10 = 6

=> 2x +16 = 6  => 2x = -10    => x = -5 

b) (3x + 2) . (2x + 9) - (x + 2) . (6x + 1) = (x + 1) - (x - 6)

=> (3x . 2x + 3x . 9 + 2 . 2x + 2 . 9) - (x . 6x + 1x + 2 . 6x + 2 .1) = x + 1 - x + 6

=> (6x2 + 31x + 18) - (6x2 + 13x + 2) = 7

=> 6x2 + 31x + 18 - 6x2 - 13x - 2 = 7

=> 18x + 16 = 7  => 18x = -9  => x = -0,5

c) 3 . (2x - 1) . (3x - 1) - (2x - 3) . (9x - 1) = 0

=> 3(2x . 3x - 2x - 3x + 1) - (2x . 9x - 2x - 3. 9x + 3) = 0

=> 3(6x- 5x + 1) - (18x- 29x + 3) = 0

=> 18x2 - 15x + 3 - 18x2 + 29x -3 = 0

=> 14x = 0  => x = 0.

25 tháng 8 2020

a) ( 3x + 2 )( x - 1 ) - ( x + 2 )( 3x + 1 ) = 7

<=> 3x2 - x - 2 - ( 3x2 + 7x + 2 ) = 7

<=> 3x2 - x - 2 - 3x2 - 7x - 2 = 7

<=> -8x - 4 = 7

<=> -8x = 11

<=> x = -11/8

b) ( 6x + 5 )( 2x + 3 ) - ( 4x + 3 )( 3x - 2 ) = 8

<=> 12x2 + 28x + 15 - ( 12x2 + x - 6 ) = 8

<=> 12x2 + 28x + 15 - 12x2 - x + 6 = 8

<=> 27x + 21 = 8

<=> 27x = -13

<=> x = -13/27 

c) 2x( x + 3 ) - ( x + 1 )( 2x + 1 ) - 5 = 9

<=> 2x2 + 6x - ( 2x2 + 3x + 1 ) - 5 = 9

<=> 2x2 + 6x - 2x2 - 3x - 1 - 5 = 9

<=> 3x - 6 = 9

<=> 3x = 15

<=> x = 5

d) ( 5x + 3 )( 4x - 7 ) - ( 10x + 9 )( 2x - 3 ) = 10

<=> 20x2 - 23x - 21 - ( 20x2 - 12x - 27 ) = 10

<=> 20x2 - 23x - 21 - 20x2 + 12x + 27 = 10

<=> -11x + 6 = 10

<=> -11x = 4

<=> x = -4/11

25 tháng 8 2020

a, \(\left(3x+2\right)\left(x-1\right)-\left(x+2\right)\left(3x+1\right)=7\Leftrightarrow-8x-4=7\Leftrightarrow x=-\frac{11}{8}\)

b, \(\left(6x+5\right)\left(2x+3\right)-\left(4x+3\right)\left(3x-2\right)=8\Leftrightarrow27x+21=8\Leftrightarrow x=-\frac{13}{27}\)

c, \(2x\left(x+3\right)-\left(x+1\right)\left(2x+1\right)-5=9\Leftrightarrow3x-6=9\Leftrightarrow x=5\)

d, \(\left(5x+3\right)\left(4x-7\right)-\left(10x+9\right)\left(2x-3\right)=10\Leftrightarrow-11x+6=10\Leftrightarrow x=-\frac{4}{11}\)

15 tháng 6 2016

a) x^2+5x+6-x^2+7x-10-6=0

12x-10=0

12x=10

x=5/6

15 tháng 6 2016

Cậu ơi giúp mình 2 câu dưới nữa ược không?